Programa educativo cuidados de enfermería del paciente quirúrgico en el nivel de autocuidado de gestantes programadas para cesárea - Rebaza Zavaleta, Carmen Teodora (2023)
This research study of descriptive, pre-experimental type, whose objective was to determine the effectiveness of the educational program: "Nursing care of the surgical patient" at the level of self-care, of pregnant women scheduled for cesarean section, where he states that people learn and develop self-care practices that become habits that contribute to health and well-being. The sample consisted of 51 pregnant women scheduled for cesarean sections, who met the inclusion criteria. For data collection, a questionnaire was applied as a tool to measure the level of knowledge before and after the application of the educational program. The results obtained were: Before the educational program, 82,4% of the pregnant women scheduled for Cesarean sections presented a regular educational level; after the application of the program 98% presented a high level; In addition, a large difference was obtained (ME=3.84) between the level of knowledge of self-care before and after the application of the educational program. It was concluded that the "nursing care" educational program is effective